Rancang Bangun Aplikasi Toko Sepatu Bekas Berbasis Website - Pujianto; Febriawan, Rangga; Renaldi, Chendi; Widodo, Suyud (Jurnal Ilmiah Sistem Informasi (JISI), 2025)
Conventional sales of used shoes still face various limitations, including limited market reach, difficulty displaying product variations, and inefficient transaction and stock management processes. These issues result in low marketing effectiveness and an increased potential for errors in transaction recording. This research aims to design and develop a web-based e-commerce platform focused on online used shoe sales as a solution to these constraints. The system was developed using a waterfall model approach, encompassing the stages of needs analysis, system design, implementation, testing, and maintenance. The website was developed using the PHP programming language with the CodeIgniter 4 framework and the MySQL database management system. Testing was conducted using black-box testing to verify the suitability of the system's functionality to user needs. The implementation results showed that the system is capable of providing key features such as a used shoe catalog, product search, user account management, checkout process, and transaction reporting. Overall, the developed platform has been proven to improve sales management efficiency, expand market reach, and reduce the potential for errors in the transaction process. Thus, this system contributes to the optimization of the digitalization of micro-enterprises in the used goods trade, particularly in the shoe sales sector, through integrated and easily accessible technology solutions.